Assessment of relevant fungal species in clinical solid wastes - Ali Noman, Efaq; Algheethi -, Adel Ali Saeed Abduh; Nik Ab. Rahman, Nik Norulaini; Nagao, Hideyuki; Ab Kadir, Mohd Omar (Springer, 2016)
The study aimed to determine the fungal diversity in clinical waste samples from a healthcare facility in Penang Malaysia. Different fungi species were detected in 83.75 % of the 92 clinical waste samples that were screened from different sections of the healthcare facility. One hundred fifty fungal isolates comprising of 8 genera and 36 species were obtained. They were purified by using single spore isolation technique. Subsequently, the isolates were identified by phenotypic method based on morphological and culture characteristics on different culture media. Among all fungal isolates, Aspergillus spp. in section Nigri 10.2 %, Aspergillus niger 9.5 %, Aspergillus fumigatus 8.8 %, Penicillium. simplicissium 8 %, Aspergillus tubingensis 7.3 %, Aspergillus terreus var. terreus 6.6 %, Penicillium waksmanii 5.9 % and Curvularia lunata 6.5 % were the most frequent. Among five sections of the Wellness Centre, the clinical wastes collected from the diagnostic labs of haematology section had the highest numbers of fungal species (29 species). Glove wastes had the highest numbers of fungal species (19 species) among 17 types of clinical wastes screened. Among all fungal species, Aspergillus spp. exhibited higher growth at 37 °C than at 28 °C, indicating the potential of these opportunistic fungi to cause diseases in human. These results indicated the potential of hospital wastes as reservoirs for fungal species.